Memórias de luta, lutas pela memória: o Reassentamento São Francisco de Assis (1995- 2008) - Pagliarini Junior, Jorge (2009)
This research intends to discuss about the territory construction for the inhabitants of the São Francisco de Assis Resettlement (Cascavel-PR), an agricultural resettlement created after a strike between a Paraná southwestern movements with the Paraná State, when it had been constructing the Salto Caxias Hydroelectric. Therefore, taking as base the memories study of the involved inhabitants in the strike and from those who purchase properties in the re-settlement 10 years after its construction, it is noticed current disputes in the life inside the re-settlement as well as in the cities nearby. Those are places that also are part of the territory to be reconstructed. The four chapters that constitute this work, it is highlighted how the conflicts in and through the territories are constituted from politics, economic and identity disputes; they are permeated by the dispute for the past, that is, from the different ways how the past is used for the identity construction and a kind of justification for the right of use of the land and the city